44.6k views
3 votes
Evaluate.     −64125‾‾‾‾‾√3

Evaluate.     −64125‾‾‾‾‾√3-example-1

2 Answers

1 vote
-4/5 is correct, since (-4/5)³ = -4*-4*-4/(5*5*5) = -64/125 
User Samuel Meddows
by
6.4k points
3 votes

The given expression is :
\sqrt[3]{(-64)/(125)}

64 can be written as 4x4x4=
4^(3)

125 =5x5x5=
5^(3)

The given expression can be written as :


\sqrt[3]{(-64)/(125)} =\sqrt[3]{((-4)^(3))/(5^(3))} =[( (-4)/(5))^(3) }]^(1)/(3)

Applying power rule of indices :

Powers are multiplied .


(1)/(3) times 3 = 1.

=
(-4)/(5)

The first option
(-4)/(5) is the right asnwer

User Ethanabrooks
by
6.3k points